2006
DOI: 10.1128/ec.5.2.330-346.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale Analysis Reveals Sst2 as the Principal Regulator of Mating Pheromone Signaling in the Yeast Saccharomyces cerevisiae

Abstract: A common property of G protein-coupled receptors is that they become less responsive with prolonged stimulation. Regulators of G protein signaling (RGS proteins) are well known to accelerate G protein GTPase activity and do so by stabilizing the transition state conformation of the G protein ␣ subunit. In the yeast Saccharomyces cerevisiae there are four RGS-homologous proteins (Sst2, Rgs2, Rax1, and Mdm1) and two G␣ proteins (Gpa1 and Gpa2). We show that Sst2 is the only RGS protein that binds selectively to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 149 publications
7
80
0
Order By: Relevance
“…Three mutants formed normal perithecia but ejected no (⌬nim-1), few (⌬mst-1), or white ascospores (⌬vel; 20% of ascospores were white.). One of the S. cerevisiae vel homologs, cla4, is required for normal pheromone sensitivity (10,41). This suggests that Cla4p acts at an earlier point in sexual development in yeast than VEL in Neurospora.…”
Section: Resultsmentioning
confidence: 88%
“…Three mutants formed normal perithecia but ejected no (⌬nim-1), few (⌬mst-1), or white ascospores (⌬vel; 20% of ascospores were white.). One of the S. cerevisiae vel homologs, cla4, is required for normal pheromone sensitivity (10,41). This suggests that Cla4p acts at an earlier point in sexual development in yeast than VEL in Neurospora.…”
Section: Resultsmentioning
confidence: 88%
“…matin structure (66,67). We have also shown previously that Asc1 interacts weakly with the G␣ in the pheromone response pathway, Gpa1, and deletion of ASC1 results in cells that are slightly more sensitive to pheromone stimulation (39). Such diversity of function has no precedent among the more "typical" G␤ subunits.…”
Section: Discussionmentioning
confidence: 97%
“…Yeast shuttle plasmids pRS315-ADH (CEN, amp R , LEU2, ADH1 promoter/terminator) and pRS316-ADH (CEN, amp R , URA3, ADH1 promoter/terminator) (38) were modified by PCR amplification of the gene of interest and subcloned such that a FLAG (GATTA-CAAGGATGACGACGATAAG) or Myc (GAACAAAAATT-GATTTCTGAAGAAGATTTG) epitope could be added to the 5Ј coding sequence of any gene with a SacI site engineered inframe with the open reading frame. Previously described yeast shuttle plasmids used in this study are pAD4M-GST (38) and pAD4M-GPA2-GST (39). The FRE-lacZ transcription reporter plasmid was generously provided by Gerald Fink (40).…”
Section: Methodsmentioning
confidence: 99%
“…Asc1p's involvement in cellular signal transduction prompted us to investigate Asc1p-sensitive protein phosphorylation beyond its own phosphorylation. Previous studies reported that the absence of Asc1p leads to increased phosphorylation of the MAPKs Kss1p and Slt2p, which control filamentous growth, mating, and cell wall integrity (2,29). In the present study, we additionally analyzed the phosphorylation of the MAPK of the high-osmolarity response pathway, Hog1p, by using an antibody specific for this protein phosphorylated at residues T174 and/or Y176 by its upstream mitogen-activated protein kinase kinase (MAP2K), Pbs2p.…”
Section: Figurementioning
confidence: 99%